The Role of Easy Songs by JVKE in Improving Vocabulary Learning among Beginners - Deni Kurniawan; Felda Ratimaya; Cici Situmorang; Iyos Munidah Tussahihah; Sallammatul Ummah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary mastery is a major challenge for beginner-level English as a Foreign Language (EFL) learners, especially when the teaching methods tend to be monotonous. This study aims to explore the effectiveness of the song